Pengaruh Laba Akuntansi Dan Arus Kas Operasi Terhadap Return Saham - Ardian, Tiara Clarisa; Devi, Yulistia; Saefurrohman, Ghina Ulfa (Universitas Islam Negeri Raden Intan Lampung, 2023)
Accounting profit information is considered relevant if it causes a market reaction by investors. The market reaction is indicated by changes in stock returns. The higher the value of accounting profit, it will cause a positive reaction, namely increasing stock returns because the company is considered to have good performance and is able to provide good returns to investors. While operating cash flow is a change in cash flow from operating activities will give a positive signal to investors, as a result investors will buy shares of the company which in turn increases stock returns. The purpose of this study was to determine the effect of accounting profit and operating cash flow on stock returns in companies listed on JII for the 2017-2019 period, either simultaneously or partially. This research is the type of data used in this study is quantitative data, using secondary data in the form of financial statements registered in the Jakarta Islamic Index for the 2017-2019 period. The results of this study are, accounting earnings have a significant effect on stock returns. This means that companies that have the ability to generate profits tend to increase their share prices. Operating cash flow has a significant effect on stock returns. This means that the amount of cash flows from operating activities determines whether the company can generate sufficient cash flows to repay loans, maintain the company's operating capabilities, pay dividends and make new investments without relying on external funding sources. Accounting profit and operating cash flow simultaneously or together have a significant effect on stock returns. Similar to the company's cash flow, the higher the cash flow value of a company, both operational cash flow, funding cash flow, and investment cash flow, the investor confidence will be higher compared to companies that have low cash flow values. In Islamic economics, investment is a muamalah activity that is highly recommended, because by investing your assets become productive and also bring benefits to others.